2018
DOI: 10.21767/2572-5394.100048
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol does not Correlate with Metabolic Syndrome Markers or Subjective Stress in Overweight Children

Abstract: Objective Being overweight is a risk factor for metabolic syndrome in children, but not all overweight children develop metabolic syndrome. Cortisol excess from chronic psychological stress has been proposed as an independent risk factor for metabolic syndrome in this already at-risk population. The present study assesses the relationship of biochemical and body composition radiographic markers of metabolic syndrome to salivary cortisol and self-report of chronic psychological stress in a cohort of overweight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Moreover, other studies also did not observe any associations between these anthropometric measures and HCC in children [49,50]. We also did not observe any prospective or cross-sectional associations of overall metabolic risk with HCC outcomes, which is generally consistent with previous studies that examined some of these relationships using hair, urinary, or salivary cortisol [44,51,52]. Our results therefore suggest that adiposity and cardiometabolic health may not be strong determinants of HCC in children.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, other studies also did not observe any associations between these anthropometric measures and HCC in children [49,50]. We also did not observe any prospective or cross-sectional associations of overall metabolic risk with HCC outcomes, which is generally consistent with previous studies that examined some of these relationships using hair, urinary, or salivary cortisol [44,51,52]. Our results therefore suggest that adiposity and cardiometabolic health may not be strong determinants of HCC in children.…”
Section: Discussionsupporting
confidence: 90%
“…30,31 In contrast to sleep, there is a lack of agreement on the relationship between stress and MetS. Although some investigators found no correlation between cortisol levels and risk of MetS, 32,33 others found a positive relationship between psychosocial stress and an increased risk of MetS. 34,35 Unhealthy lifestyles, including unhealthy diet and sedentary behavior, may increase the risk of MetS.…”
mentioning
confidence: 99%